The Joy and Light Bus Company [large type] - McCall Smith, Alexander, 1948- (McCall Smith, Alexander, 1948- No. 1 Ladies Detective Agency series, 2021)
"Mr. J.L.B. Matekone is unsure about how to grow the successful Tlokweng Road Speedy Motors. When an old friend approaches him about a new business venture, Mr. Matekone would need to mortgage his property to pursue this endeavor. Mma Ramotswe and Mma Makutsi wonder what this will mean for his current business--as well as their own. And Botswana's premier detective agency agree to investigate when a concerned son learns that his aging father's nurse now stands to inherit the family home, and he begins to doubt her intentions. Tricky as these matters may be, Mma Ramotswe and Mma Makutsi will rely on their tact, humor, and goodwill to ensure that all involved find the happiness they deserve"--